A research paper on corporate responses to natural calamities in Iloilo City - Calibjo, Kenneth; Gortayo, Sheila Anne; Mobo,Jenel; Mary Hyacinth, Odunwa; Valderrama, John Dexter; Villa, Eloisa Rose
Almost a year ago, Iloilo experienced one o the most devastating natural calamities that caused severe damage to the community. Numerous civic organizations and other concern individuals extended their help to victims of the said calamity, This is one instance wherein some media organizations, despite the help that they extend, find a chance to take advantage of the situation to further promote their good names, products and services. This study is anchored mainly on the concept of corporate social responsibility (CSR). The researchers attempted to categorize the media organizations' responses whether it is a form of advertising or purely an act of kindness. These responses are divided into two cases, as highlighted by Z100 University station and GMA regional Network Group. Corporate responses, in general, vary depending on the situation at hand. The larger the company is, the more assistance they can offer to a wider scope of beneficiaries. There are also other that do this purely for business. These responses are affected by the several factors that the researchers have identified in the conduct of the study.